2017
DOI: 10.1038/s41598-017-08343-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GOLPH3 on cumulus granulosa cell apoptosis and ICSI pregnancy outcomes

Abstract: Previous studies have shown that GOLPH3 mediates cell growth, proliferation and differentiation and inhibits cell apoptosis; however, the role of GOLPH3 in cumulus granulosa cells and the value of GOLPH3 in predicting ICSI pregnancy outcomes remain unknown until now. Our findings showed higher positive expression rate, score of staining intensity, and immunohistochemical score of GOLPH3 in the cumulus granulosa cells of the pregnant women relative to non-pregnant women, and a higher apoptotic rate of cumulus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
1
7
1
Order By: Relevance
“…Likewise, we found significantly lower percentages of apoptotic CCs in women achieved chemical and clinical pregnancy plus live birth compare to nonpregnant women in both PCOS and TF infertility groups. In line with our results, it is confirmed that percentage of apoptosis in CCs among women who became pregnant is significantly fewer than women who did not achieve pregnancy (Lin et al, ; Ruvolo et al, ). With regard to early pregnancy loss, we found that the apoptotic cumulus cells are significantly higher in women with early pregnancy loss among the patients with PCOS but not in the TF fertility group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, we found significantly lower percentages of apoptotic CCs in women achieved chemical and clinical pregnancy plus live birth compare to nonpregnant women in both PCOS and TF infertility groups. In line with our results, it is confirmed that percentage of apoptosis in CCs among women who became pregnant is significantly fewer than women who did not achieve pregnancy (Lin et al, ; Ruvolo et al, ). With regard to early pregnancy loss, we found that the apoptotic cumulus cells are significantly higher in women with early pregnancy loss among the patients with PCOS but not in the TF fertility group.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier reports showed the higher percentages of apoptotic cumulus cells among immature oocytes compared with mature ones (Host, Gabrielsen, Lindenberg, & Smidt‐Jensen, ) as well as women who achieved pregnancy compared with who did not (Ruvolo, Fattouh, Bosco, Brucculeri, & Cittadini, ). In addition, apoptosis of cumulus cells is considered as a new indicator for the prediction of in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI; Lee et al, ; Lin et al, ). On the other hand, time‐lapse system (TLS), which has been recently introduced to ART laboratories, provides additional data on both morphologic and the exact timing of embryo development entitled "morphokinetic variables" that could improve ART outcome compared with a standard incubator (Adamson et al, ; Fishel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al ( 71 ) found no difference in TUNEL staining and caspase activity until the LH surge, whereas caspase activity for the combined caspases 1–9 was present before the LH surge but then disappeared after the LH surge ( 71 ). In a recent study, the same technique of counting pyknotic cells found that the level of apoptosis was reduced in patients who became pregnant ( 80 ). The finding was supported by qPCR data of a greater level of caspase 3 in the non-pregnant group.…”
Section: The Relationship Between Apoptosis and Oocyte Qualitymentioning
confidence: 98%
“…Surgeon Patrick Steptoe was awarded the Nobel Prize in 2010 for his work at the time (4). Despite all the advanced techniques provided in the scope of assisted reproductive techniques, pregnancy cannot be achieved in approximately 40% -50% of the patients undergoing the procedure (5). Selection of the best quality sample from the oocyte pool has a great importance in the success achieved by assisted reproduction techniques (ART).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand high quality oocyte selection is expected to increase implantation and pregnancy rates (5,7). It has been shown in many studies that the perfect two-way interaction between oocyte and surrounding somatic cells (granulosa, cumulus cells) is highly determinant in egg quality (6,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%